Non-Tariff Measures on Goods Trade in the East African Community : Synthesis Report - World Bank (Washington, DC, 2014)
The purpose of this note is to highlight the key findings of an assessment of non-tariff measures (NTMs) on goods trade in the East African Community (EAC), and identify priorities for a second stage of work focused on practical steps toward reducing and eliminating these NTMs. This synthesis report is prepared in response to EAC's request for a phased technical assistance from the World Bank. Its objectives are to choose NTMs with high impact on inter-member trade out of the range of NTMs identified in the region; improve the understanding of their persistence over time; and, devise practicable implementation plans for their 'removal.' In concrete steps towards establishing a free trade area (FTA), the EAC has already made remarkable progress on reducing eliminating tariffs on traded goods since 2005. The remaining internal tariff walls are to be eliminated by 2010. There is increasing need for the kind of analysis requested by EAC where the regional economic community (REC) wide internal trade liberalization has allowed considerable reduction/elimination of tariffs, but would be offset by NTMs. This, in turn would significantly delay the establishment of the EAC common market.